PENGARUH KOMPLEKSITAS TUGAS DAN AUDIT FEE TERHADAP KUALITAS AUDIT DENGAN PARAMETER KONFLIK DISKRIMINASI HARGA - Jessica Regata Melanie (2023)
This study examines whether price discrimination based on audit firms' reputation occurs against audit firms internationally affiliated and non-internationally affiliated which affects the relationship between task complexity and audit fees on audit quality. This research is a quantitative study with a questionnaire and a Likert scale as a measuring tool. The population of this research is auditors of audit firms in DKI Jakarta. Using a purposive sampling technique, of the 273 questionnaires distributed and 135 returned questionnaires, only 117 questionnaires could be processed. The analytical method used is Structural Equation Modeling (SEM) analysis. The results of the study show that task complexity has a significant negative effect on audit quality. Price discrimination based on audit firms' reputation can weaken the relationship between task complexity and audit quality. Meanwhile, audit fees do not have a significant positive effect on audit quality either independently or when moderated by price discrimination based on audit firms' reputation. However, it was found that there is a direct effect of price discrimination on audit quality. Researchers apply additional tests by comparing the results of analysis of audit firms with international affiliates and non-internationally affiliated. There is no significant difference from the results of the analysis on data with audit firms non-internationally affiliated. However, the researcher found that only task complexity had a negative significant effect on audit quality in the results of data analysis with audit firms internationally affiliated.